Caracterização de amostras de bauxita visando a aplicação de métodos de concentração gravítica - Diego de Souza Arenare (2009)
Bauxite Rock is a impure mixture of aluminum minerals, being gibbsite - -Al(OH)3, diaspore - -AlO(OH) and bohemite - -AlO(OH) the most importants. These minerals are aluminum oxi-hydroxes and their proportions in the rock are very variable, just as the kind and quantity of impurities (iron oxides hematite and goethite; aluminossilicates kaolinite; quartz, etc. Bauxite dressing is done by a much simple way, consisting of crushing and washing to withdraw the mud, which contains most part of aluminossilicates (reactive silica). High grade alumina is obtained by the Bayer process, which consists in the digestion of aluminum minerals, especially gibbsite. The latter becomes soluble while the other contaminants are insoluble at very alkaline pH conditions prevalent in the Bayer process reactors. Currently, mining companies of various sectors (iron, basic metals, industrial minerals) has turned their attention to the decrease of quality of mineral reserves, and the necessity of exploring low grade reserves, taken as marginal deposits until the moment. Aluminum producers are, in the same way, looking for process routes which could allow the profit of beds of bauxite deposits considered inappropriate for Bayer process until now. Samples of three different levels of a bauxite deposit (nodular bauxite, laterite and Massive bauxite in natura) owned by Alcoa (Juruti-PA), were characterized aiming application of gravity concentration. Results showed a correlation in particles between presence of silicon and iron in nodular bauxite and laterite samples. This is relevant once silicon content could reduce through removing iron rich fraction. However, gravity concentration criteria showed values close to application limit, indicating difficulty of separation. Jig tests did not showed good results, while spiral tests showed improvements in alumina grade and in relation alumina/silicon for nodular bauxite and laterite.